The Cat in the Hat - Seuss Dr. (New York Random House, 1957)
Two children sitting at home on a rainy day are visited by the Cat in the Hat who shows them some tricks and games.
Keywords: Cat in the Hat (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Cats -- Fiction; Stories in rhyme